Intervenção numa indústria de montagem de hidrômetros: recomendações de melhorias baseadas numa avaliação ergonômica - Ribeiro, Gabriela; Leite, Charles [UNESP]; Neves, Flavia; Martins, Laura; Arezes, P.; Baptista, J. S.; Barroso, M. P.; Carneiro, P.; Costa, N.; Melo, R.; Miguel, A. S.; Perestrelo, G.; et al. (Portuguese Soc Occupational Safety & Hygiene, 2013)
This paper addresses the manual assembly equipment. Theme profusely exploited by subjecting workers to several ergonomic constraints associated with the splitting of the task, facilitating the monotony and high number of repetitive movements, which may result in illnesses from physical and psychic. In conducting this research, we proposed design requirements improvement initially found to problems in order to subsidize comfort, safety and quality of life for workers of a French company, maker of hydrometers volumetric and velocimetric, installed in Brazil. Based on systemic approach considering human interface task-machine-environment, the results indicated that the factory exposes its workers to problems of physical-environmental, organizational, workplace, biomechanical and psychosocial. Were proposed changes and adjustments in working conditions of employees surveyed in order to subsidize comfort, safety and quality of life to these people.
Intervention in hydrometers industry: recommendations for improvements based on ergonomic assessment
Intervention in hydrometers industry: recommendations for improvements based on ergonomic assessment
Keywords: Human Costs; Systems Approach; Human Factors; Biomechanical Analysis; Anthropometric Analysis